Impact of Gold Price and Oil Price on the Indian Stock Market : With Special Reference to the Bombay Stock Exchange Market - Joseph, Binu; U.R., Rajeshwari (Indian Journal of Research in Capital Markets, 2023)
Purpose : This study aimed to investigate the causative relationship between oil, gold, and the stock market and the effects of gold and oil prices on the stock market, focusing on the BSE SENSEX. Methodology : Daily data were used in the study for the sampling period spanning from January 1996 to October 2022. The factors under investigation were the price of gold, the BSE SENSEX, and WTI crude oil. The most closely followed bellwether indicator in India is the BSE SENSEX. SENSEX aims to assess the performance of the 30 largest, most liquid, and soundest financial companies listed on the BSE Ltd. in India’s several economic sectors. Gold, oil, and stock prices were all analyzed using the vector autoregression (VAR) model. When one or more variables in a model change, the impulse response function (IRF) has been used to explain how the variables in the model change as well. Findings : No long-term correlation was found in this analysis between the prices of stocks, gold, and oil. The long-term relationship (co-integration) between stock, gold, and oil prices was not found in this study. The oil price influenced both the gold price and the SENSEX in the short term. The analysis also showed that the price of gold and the SENSEX were causally related in a one-way fashion. Originality : The short- and long-term effects of gold prices on macroeconomic factors like inflation, growth rates, exchange rates, employment effects, and monetary policy have all been studied in economic research. However, little research has been done on how changes in the price of gold and oil affected the SENSEX.